Modern View on the Problem of Choosing a Vaccine against Hepatitis B - V. P. Chulanov; T. A. Semenenko; I. V. Karandashova; S. V. Komarova; D. S. Kostyushev; A. P. Suslov; E. V. Volchkova (Эпидемиология и вакцинопрофилактика, 2017)
The problem of the discrepancy between serotypes of the circulating strains of hepatitis B virus and serotype of the HBsAg in the vaccine is discussed. The results of published scientific studies show that hepatitis B vaccines containing HBsAg serotype ad provide good, but not optimal, protection against heterologous serotypes of the virus. The authors conclude that the use of vaccines containing HBsAg serotype typical for given territory is a priority. Further in-depth studies on this issue are needed to clarify the available scientific evidence.